2020
DOI: 10.1037/edu0000440
|View full text |Cite
|
Sign up to set email alerts
|

Social, dimensional, and temporal comparisons by students and parents: An investigation of the 2I/E model at the transition from elementary to junior high school.

Abstract: The present research examined the joint effects of social, dimensional, and temporal comparisons on students’ academic self-concepts and parents’ beliefs about their children’s competencies during students’ transition phase from elementary school to junior high school. To this end, we tested the newly developed 2I/E model using longitudinal data including 2,417 students between Grades 6 and 7 and 1,846 parents. We found strong social comparison effects and moderate dimensional and temporal comparison effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Future research should, therefore, aim to examine how individual and shared math-related gender stereotypes relate to changes in students’ self-concepts. In particular, it would seem worthwhile to conduct such investigations during phases of school transitions, which have shown to come along with significant changes in students’ self-concepts (e.g., Wigfield et al, 1991 ; Wolff et al, 2020c ), given that these changes might also result from changes in gender stereotypes shared within the classroom. Moreover, it would be advisable for future research to measure students’ gender stereotypes (and other covariates) some time before the self-concepts as such a design would be more suitable to allow an approximation to causal conclusions than the simultaneous assessment of these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should, therefore, aim to examine how individual and shared math-related gender stereotypes relate to changes in students’ self-concepts. In particular, it would seem worthwhile to conduct such investigations during phases of school transitions, which have shown to come along with significant changes in students’ self-concepts (e.g., Wigfield et al, 1991 ; Wolff et al, 2020c ), given that these changes might also result from changes in gender stereotypes shared within the classroom. Moreover, it would be advisable for future research to measure students’ gender stereotypes (and other covariates) some time before the self-concepts as such a design would be more suitable to allow an approximation to causal conclusions than the simultaneous assessment of these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the 2I/EM assumptions have found support in 11 empirical studies (Wolff, Helm, et al, 2019; Wolff, Helm, Zimmermann, et al, 2018; Wolff, Nagy, et al, 2019; Wolff, Wigfield, Möller, Dicke, & Eccles, 2019). Usually, these studies have revealed strong positive social comparison effects, moderate negative dimensional comparison effects, and small positive temporal comparison effects across student samples of different age groups, school types, and countries.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A few studies have tested the 2I/EM while controlling for students’ prior self-concepts, measured before the first achievement measure (Wolff, Wigfield, et al, 2019; Wolff, Nagy, et al, 2019, Study 4; see also Figure 4). In accord with the RI/EM, these studies assumed and found support for positive effects of self-concepts on self-concepts within subjects (ε), and near-zero effects of self-concepts on self-concepts between subjects (η).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…1Note that other work also focused on dimensional comparisons (i.e., comparisons between different school subjects) in parent assessments of students’ abilities (e.g., Wolff et al, 2020) and teacher assessments of students’ ability self-concepts (e.g., Dickhäuser, 2005; Helm et al, 2018). Also studies investigating halo effects on teacher judgments across different school subjects target dimensional comparisons (e.g., Dompnier et al, 2006; Stang & Urhahne, 2016a).…”
mentioning
confidence: 99%